Preventing Violence and Extremism in Indonesian Educational Institutions: Policies and Strategies - Mubarak, M. Zaki; Zuliha Binti Razali, Siti (KnE Social Sciences, 2022)
This article discusses the policies and strategies of the Indonesian government for preventing the influence of radical and extreme religious ideologies in schools and universities. In their survey, PPIM UIN Jakarta in 2019 and the Wahid Institute in 2020 found that Indonesian educational institutions, from high schools to universities, were vulnerable to the influence of extreme views and intolerance. This article examines a number of elements that play a strategic role in preventing violence and extremism in educational institutions, such as government regulations; education curriculum; and the role of internal and external stakeholders, including teachers, parents, students, government officials, and civil society. The authors argue that the strategies and policies of each university and school in preventing radicalism among students have different levels of effectiveness. Synergies involving stakeholders also contribute to the success and failure of securing educational institutions from the dangers of violence and extremism. The results of this study are based on in-depth interviews with a number of selected sources. This paper recommends the need to synchronize strategies and policies related to the prevention of extremism and violence in educational institutions and the more effective participation of all stakeholders. Keywords: preventing violence–extremism, educational institutions, strategies, policies, effectiveness